Effects of extensive reading and translation activities on grammar knowledge and attitudes for EFL adolescents. (August 2015) - Lee, Juhee; Schallert, Diane L.; Kim, Eonsil
Abstract: Despite evidence of an association between L2 reading and grammar knowledge by way of research on the role of grammar in reading comprehension, few scholars have investigated the reverse relation, the contribution of reading to grammatical knowledge. In this study, we investigated the effects of two types of reading instruction, extensive reading and translation, on knowledge of general grammar and specific syntactic features (articles and prepositions) as well as learner attitudes. Participants ( N = 124) were adolescent EFL learners in South Korea, who received either extensive reading or translation instruction for two academic semesters. From analysis of their responses to linguistic tests and an attitude survey, results suggested that extensive reading and translation activities had differentiated effects on learners' grammar knowledge and attitudes depending on their L2 proficiency. Although both forms of instruction showed positive gains in grammar knowledge from pretest to later tests, extensive reading seemed to have a negative impact on attitude measures for students of low proficiency but produced positive outcomes for high level students on both attitudes and linguistic measures. Alternatively, translation activities seemed beneficial to all level learners for attitudes, whereas the instruction seemed to have more positive effects for mid-proficiency learners on grammar measures.